2021
DOI: 10.3390/nu13020337
|View full text |Cite
|
Sign up to set email alerts
|

Micronutrient Adequacy in the Diet of Reproductive-Aged Adolescent Girls and Adult Women in Rural Bangladesh

Abstract: Micronutrient deficiencies remain a serious nutritional concern in Bangladesh, especially among rural women of reproductive age (WRA). This study assesses the diet quality of reproductive-aged adolescent girls and adult women (referred to together as WRA in this study), including socio-demographic factors associated with their diet quality. The diet quality of adolescent girls was compared with that of adult women to assess which group was most at risk. The diet quality was measured by calculating the nutrient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 36 publications
3
20
1
Order By: Relevance
“…Thus, lower socioeconomic status and lower education level were associated with lower dietary diversity score. Similar finding was highlighted by other studies [23,27,28,29]. However, gender, sex and anthropometric status of the participants were neither associated with their dietary diversity scores nor with the consumption of same food groups.…”
Section: Discussionsupporting
confidence: 90%
“…Thus, lower socioeconomic status and lower education level were associated with lower dietary diversity score. Similar finding was highlighted by other studies [23,27,28,29]. However, gender, sex and anthropometric status of the participants were neither associated with their dietary diversity scores nor with the consumption of same food groups.…”
Section: Discussionsupporting
confidence: 90%
“…In addition, the Nutrient Adequacy Ratio (NAR)-the ratio between the subject's actual intake and reference intake-was calculated for each nutrient (Equation 2) (Hatløy et al, 1998). Following a previous study (Akter et al, 2021) The MAR was reported on a scale from 0 to 1, with 0 indicating that the requirement for no nutrients was met and 1 indicating that the requirements for all nutrients were met.…”
Section: Dietary Data Analysismentioning
confidence: 99%
“…It was interesting that increased price only affected the quality of fish but not the quantity or variety. It is possible that since fish is the most commonly consumed animal sourced food and an integral part of the Bangladeshi diet ( 10 , 11 ), urban low-income residents compromised the quality of fish instead of reducing the intake in quantity or variety. However, further research is necessary to understand what the lower quality of fish consumption meant in terms of food safety concerns of the low-income consumers and how they coped with such concerns.…”
Section: Discussionmentioning
confidence: 99%
“…In Bangladesh, the impact of the COVID-19 pandemic was associated with a decline in consumption of fruits and vegetables, and animal source foods, such as fish and meat ( 3 – 8 ). In Bangladesh, fish is the most commonly consumed animal sourced food and an important source of macro-and micronutrients in the diet of the low-income populations ( 9 – 11 ). Consuming different fish species (variety) is important as their nutrient composition vary substantially; for example, farmed species contribute to lesser micronutrient intakes than non-farmed ones ( 12 14 ).…”
Section: Introductionmentioning
confidence: 99%